DEVONIAN STAGE BOUNDARIES ON THE EAST EUROPEAN (RUSSIAN) PLATFORM - Rzhonsnitskaya M.A. (My University, 2001)
The Devonian of the East European Platform is chiefly represented by shallow-marine rocks of Lochkovian through Famennian age. Palaeontological evidence from various groups, including condonts, palynomorphs, ostracodes, ammonoids and brachiopods, enable regional correlations. However, correlations with standard stages are not well constrained.
Keywords: Devonian; Russian Platform; Paleozoic::Devonian; Палеозой::Девонская